Solution
Given that:
Total number of messages sent is 96
Let the number of messages Yoko sent be x
=> Austin will send x - 6 (since austin sent 6 fewer messages)
=> Tom will send 3(x - 6) (since Tom sent 3 times as many messages)
Since they make a total of 96
![\begin{gathered} \Rightarrow x+x-6+3(x-6)=96 \\ \\ \Rightarrow x+x-6+3x-18=96 \\ \\ \Rightarrow5x-24=96 \\ \\ \Rightarrow5x=96+24 \\ \\ \Rightarrow5x=120 \\ \\ \Rightarrow x=(120)/(5) \\ \\ \Rightarrow x=24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jkvzkbpiyghwo8cu5qpemsd1ney8hiq1xe.png)
Hence, Yoko sent: 24 messages
Austin sent: 24 - 6 = 18 messages
Tom sent: 3(18) = 54 messanges
Number of text messages Yoko sent: 24 messages
Number of text messages Austin sent: 18 messages
Number of text messages Tom sent: 54 messanges